The Specie Standard As A Contingent Rule: Some Evidence for Core and Peripheral Countries, 1880-90. - Michael D. Bordo; Anna J. Schwartz (Rutgers University, Department of Economics, 1994)
The classical gold standard era from 1880 to 1914, when most countries of the world defined their currencies in terms of a fixed weight (which is equivalent to a fixed price) of gold and hence adhered to a fixed exchange rate standard, has been regarded by many observers as a most admirable monetary regime. They find that its benefits include long-run price level stability and predictability, stable and low long-run interest rates, stable exchange rates (McKinnon, 1988), and hence that it facilitated a massive flow of capital from the advanced countries of Europe to the world's developing countries.
Keywords: E5; 330; contingent; gold standard; rule